Evaluación de una alternativa de aprovechamiento para los biosólidos generados por plantas de tratamiento de aguas residuales (2020)
The present research work aims at the technical evaluation of an alternative use for biosolids generated in wastewater treatment plants, because biosolids are a byproduct with important characteristics has a many applications and properties to be used in different areas. This project was divided into three parts; the first one is a detailed investigation of the physicochemical and microbiological characteristics of biosolids generated especially in domestic wastewater treatment plants, selecting treatment plants that are well known in the territory to be used. They locate and have had great experience and background regarding the biosolids they produce. For the second part of the project, all those alternatives available to use biosolids and that present environmental, social and economic benefits in their use were analyzed with the best criteria and a literary search. Once the subject was understood, one of these alternatives was selected using a decision matrix which evaluated various criteria of the proposed biosolids exploitation options and after that, the best option was selected and identified.